Kilis as “little Beirut”: Shadow Markets and Illegality in the Southeastern Margins of Turkey - Hatice Pınar Şenoğuz (L'Espace Politique)
The Middle Eastern borders are not only characterized by relations of trust, straddling forms of living, kinship, familial alliance and ethnic affinity but also by transnational flows connecting these borderlands with broader commercial and financial networks across the metropolitan centers. Drawing on an ethnographic fieldwork between early 2011 and mid-2012 in Kilis border town at the Syrian frontier, this paper dwells upon the wealth generation outside the formal state and market channels on the southeastern margins of Turkey. It explores the growth of transnational shadow economy along the southeastern borders of Turkey within the context of import-substituting industrialization (ISI) of 1960-1980 and argues that it foreshadowed the neoliberal trade liberalization. ISI period was characterized by the imposition of strict regulation on the circulation of foreign exchange as well as high import tariffs and quotas in order to provide the favourable conditions for domestic industrialization.From the vantage point of a smuggler-turned-into-businessman and an extended family from rural background moving up among the ranks of urban middle class, the paper approaches the geographical border not only as territorial boundary, but also as the margins of economy and law that the dwellers sought benefiting as a mechanism of upward mobility by manipulating and circumventing them. It demonstrates how border dwellers were incorporated into the redistributive logic of shadow economy, took benefit of the protective measures by reckoning rents to the illegal entry of consumer goods as well as gold and foreign currency and made their living in a border region that lacked opportunities for regular employment and a secure salary within the framework of ISI-based development.